The Effect of Ginger Water Decoction on Leg Edema in Pregnant Mothers at Kasih Ibu Primary Clinic, 2024 - Lubis, Basyariah; Wulandari, Suci; Safrida Nuzul Hayati (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2024)
The bending of the uterus restricts venous return and gravitational pull, which increases fluid retention and causes 80% of pregnant women in the third trimester to experience leg edema or swelling. Edema in pregnant women’s legs can be a sign of dangerous pregnancy conditions, such as pre-eclampsia. Edema is also very dangerous for pregnant women as it can lead to issues with the heart, kidneys, and other body parts, disrupting their functions. Foot soaking, or foot hydrotherapy, is an additional therapy that can be done independently. To improve blood circulation and trigger a systemic response (vasodilation) through the dilation of blood vessels, bathing with warm water will help. The authors aim to conduct research on